Strengthening Civic Values Through Pesantren and Madrasah - Tim PPIM UIN Jakarta (Studia Islamika, 2008)
PPIM's programme intends to strengthen civic values in Indonesia through pesantrens and madrasahs, i.e. through in-service training for two target groups within these institutions of Islamic education (pesantren leaders [kyai/nyai] and teachers of religious subjects) in three locations on Java (West Java (including Banten), Central Java (including Yogyakarta), and East Java). This geographic limitation is in part due to the high concentration of pesantrens and madrasahs on the island, further to the fact that the areas are highly Islamized as indicated by their demands for the implementation of the shari'ah (Islamic law).DOI: 10.15408/sdi.v15i2.535